The Prominent Pioneering ‘Plateleteer’: Reflections on and Personal Reminiscences of Gustav V. R. Born (1921–2018) - Scharf, Rüdiger E. (Hämostaseologie, 2019)
Among the pioneers in platelet research, Gustav Born was perhaps the most prominent representative, just a real “plateleteer”. He achieved scientific fame for the invention and application of light transmission aggregometry. Importantly, he paved the way for contemporary antiplatelet therapy. Integrating his fundamental knowledge of platelet biology into the pathology of vascular disorders, Born provided seminal contributions to the understanding of atherogenesis and thrombogenesis. He also generated visions for pharmacological strategies that, nowadays, are translated into reality. Inside and outside of science, Born was a great man. He had a deeply held belief in humanity. In this article, his life, scientific career and achievements are appreciated together with personal reminiscences of this outstanding personality.
Keywords: Gustav Born; history of platelet research; lifetime achievements; platelet aggregometry; atherosclerosis; thrombosis